Study on the Process Optimization and Wear Resistance of Electron Beam Cladding WC-CoCr Coating on Inconel 617 Surface - Hailang Liu; Yiping Huang; Bo Wang; Xiaoyu Wang (Advances in Materials Science and Engineering)
In order to enhance the high-temperature wear resistance of the nickel-base alloy, the electron beam is used to clad the WC-CoCr composite coating on the Inconel 617 surface. A six-factor and three-level orthogonal experiment is designed using Minitab software with scanning beam current, frequency, high voltage, beam spot diameter, offset sweep amplitude, and scanning speed as variables, and the variance and range of the test results are analyzed. The optimal cladding process parameters were determined according to the influence of various factors on the quality characteristics of the cladding layer. The wear behavior at 200°C, 600°C, and 1000°C and microstructure and phase composition of coating before and after electron beam treatment were tested. The results show that the ion exchange between the coating and the substrate is carried out after electron beam treatment. The WC, CoCr, (Fe, Ni)C6, Fe3W3C phase, and solid solution of α-Co were found in the cladding layer, and the microstructure of the coating is mainly dendrite and eutectic on CoCr substrate. The test of wear behavior at high temperature shows that the wear rate of the coating treated by electron beam at 200°C, 600°C, and 1000°C is 10.14 times, 6 times, and 2.29 times lower than that of the substrate, respectively. Moreover, the furrow and scratches of the cladding layer are less than those of the substrate at high temperature. The wear resistance of the coating was improved.